Accepted or not: homosexuality, media, and the culture of silence in the Philippine society - De Leon, John Angelo; Jintalan, Joseph (Penerbit Universiti Kebangsaan Malaysia, 2018)
The presence of homosexuals in mainstream media is widespread in the Philippines. Case in point are the images of homosexuals depicted in a popular Philippine noontime variety show. As an observer, it gives an outright impression that there seems to be an acceptance of homosexuality among the Filipinos as manifested by how they are being patronized through these sketches. The aim of the paper is to investigate how Filipinos seem to have a culture of silence in terms of accepting same sex marriage despite the presence and seemingly acceptance of homosexuals in mainstream media. Through qualitative audience analysis, audience reactions were observed while watching segments of the noontime shows which depict homosexual roles. This paper argues that Filipinos seem to lose acceptance of homosexuality on the matter of basic human right such as the right to marriage and legal union due to being considered as a predominant Catholic country with its long colonial history with the Spaniards. Furthermore, the paper argues that colonial and postcolonial perspectives play a bigger role on same-sex marriage discourses. The researchers posited that there seems to be a culture of silence in Philippine society in terms of same-sex marriage because of this colonial and postcolonial ideologies. This implies a continuiung cycle of cultural and ideological reproduction on matters concerning homosexuality. The kind of mindset passed through culture and social institutions, like the church, sustains this culture of silence. Likewise, the culture of silence reinforces the colonial and postcolonial perspectives on same-sex marriage and homosexuality.